Multi-objective capacity programming and operation optimization of an integrated energy system considering hydrogen energy storage for collective energy communities - Wang, Jinshi; Xue, Kai; Guo, Yanjun; Ma, Jinpeng; Zhou, Xuan; Liu, Ming; Yan, Junjie (Energy conversion and management, 2022)
•An integrated energy system combining hydrogen energy storage was designed and assessed.•A hybrid operation strategy following objective function was proposed.•Capacity planning was developed considering energy, economy, environment and grid dependence.•The annual hydrogen supply of optimum scheme is as high as 81,673 kg.•The sensitivity analysis of device efficiencies and market factors was conducted. A novel grid-linked integrated energy system design combined with hydrogen energy storage for collective energy communities has been proposed and analyzed, which is driven by natural gas and solar energy to achieve coordinated supply of cooling, heating and power. The models of energy devices were established in detail, and a multi-variable multi-objective mixed integer nonlinear programming coupling maximum rectangle method and particle swarm optimization was adopted. The optimal configuration and indicators were obtained based on the comprehensive assessment of energy, economics, environment and grid dependence. A hybrid operation strategy following objective function has been developed to improve the overall performance. A real case in Xi’an of Northwest China was chosen to study according to the simulated load demand, three operation strategies were compared, hourly energy management was assessed, and four electrical energy storage schemes were contrasted. Finally, the scheme that uses surplus electricity to electrolyze water for producing hydrogen to supply consumers under hybrid operation strategy is the optimum selection and the annual hydrogen supply is as high as 81,673 kg. Besides, the effects of main device efficiencies, natural gas price and electricity price on system performance were discussed. The results indicated that the power generation efficiency of gas turbine and market factors have the most conspicuous impact on the proposed system. This work may provide theoretical guidance for relevant research and application.